2010
DOI: 10.1366/000370210792434396
|View full text |Cite
|
Sign up to set email alerts
|

What is the Origin of Positional Fluctuation of Spectral Features: True Frequency Shift or Relative Intensity Changes of Two Overlapped Bands?

Abstract: We investigated what is really meant by so-called positional or frequency fluctuation of spectral features. To show the difference between the true frequency shift of a single band and apparent peak maximum shift caused by relative intensity changes of overlapped adjacent bands, we analyzed infrared (IR) spectra of the OH stretching band of ethylene glycol during the heating process and the C=O stretching band of acetone in a mixed solvent CHCl(3)/CCl(4) with varying solvent compositions. These spectra are wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…In the spectra collected after the fourth (t = 101 min) and the fifth pulses (t = 166 min), an increase in the intensity of the absorption bands associated to superficial sulfates/sulfites can be observed, accompanied by a shift from 1372 to 1381 cm 1 and from 1065 to 1052 cm 1 , respectively. The observed shift may be explained either by the combined effect of two overlapping bands that change in relative intensity or by a pure frequency shift of a single band induced by the change in the strength of molecular interactions 52 . Furthermore, a shoulder appears at 1205 cm 1 , associated with the formation of bulk-like sulfate species 18,26,31,50,51 .…”
Section: Analysis Of Stem Imagesmentioning
confidence: 99%
“…In the spectra collected after the fourth (t = 101 min) and the fifth pulses (t = 166 min), an increase in the intensity of the absorption bands associated to superficial sulfates/sulfites can be observed, accompanied by a shift from 1372 to 1381 cm 1 and from 1065 to 1052 cm 1 , respectively. The observed shift may be explained either by the combined effect of two overlapping bands that change in relative intensity or by a pure frequency shift of a single band induced by the change in the strength of molecular interactions 52 . Furthermore, a shoulder appears at 1205 cm 1 , associated with the formation of bulk-like sulfate species 18,26,31,50,51 .…”
Section: Analysis Of Stem Imagesmentioning
confidence: 99%
“…SMCR result of the temperature-dependent IR spectra of ethylene glycol was previously reported 3 The maximum position ν max of the composite peak can be obtained from the experimentally observed spectra. Combined with the band positions ν 1 and ν 2 of the pure component spectra obtained from SMCR, (ν 1 -ν max )/(ν 1 -ν 2 ) was calculated.…”
Section: -5mentioning
confidence: 84%
“…It is in good agreement with our previous results that there are two distinct species, probably the hydrogen bonded and either nonhydrogen bonded or substantially weakly bonded ethylene glycol, which change their relative populations with temperature. 3 …”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…18 It was found that the spectral dataset containing a real band frequency shift requires substantially more principal components (PCs) than normal PCA situations to adequately capture the detailed intensity variations arising from the nonlinear effect. This is because the shifting peak cannot be described as a simple linear combination of other peaks located at different frequencies.…”
Section: Introductionmentioning
confidence: 99%